Computer science : course conpanion - Mackenty, Bill (Oxford : Oxford University Press, 2025)
A comprehensive course book designed to support both Standard Level and Higher Level IB DP Computer Science aligned with the 2025 syllabus, including worked examples, programming guidance, and real-world contexts.
(3z(BIB-approved content aligned to the 2025 subject guide.(3y (B(from publisher) :s
Keywords: Computer science -- Textbooks; Computer science$1 (BStudy and teaching (Secondary)s -- Textbooks; Programming (Computer science) -- Textbooks